EVALUASI LEVEL OF SERVICE MELALUI KONFIGURASI SPASIAL BERBASIS SPACE SYNTAX PADA TERMINAL 3 DOMESTIK SOETTA: Evaluating Level of Service Through Space Syntax-Based Spatial Configuration Analysis at Terminal 3 Domestic, Soekarno–Hatta International Airport - Dwinanto Dwinanto (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2026)
Abstract: This study aims to evaluate the relationship between spatial configuration and Level of Service (LoS) within the domestic terminal using the Space Syntax approach and IATA Airport Development Reference Manual (ADRM) 12th Edition. The research employed a quantitative-descriptive method through Visibility Graph Analysis (VGA) using DepthmapX to assess spatial integration, connectivity, and intelligibility across the main passenger processing areas, including check-in hall, security checkpoint, boarding lounge, baggage claim hall, and arrival hall. LoS evaluation was conducted based on peak hour passenger demand, queue capacity, processing time, and spatial capacity standards. The results indicate that the terminal has a strong linear spatial structure with high integration values along the main circulation corridors, supporting efficient passenger movement and orientation. However, several high-demand areas, particularly the check-in hall and baggage claim hall, still experience sub-optimum operational performance despite having adequate spatial capacity. The study concludes that effective terminal performance is influenced not only by spatial configuration but also by operational processing capacity and passenger flow distribution. Keyword: Space Configuration, Level of Service, Passenger Circulation, Airport Terminal, Visibility Graph Analysis Abstrak: Penelitian ini bertujuan mengevaluasi hubungan konfigurasi spasial terhadap Level of Service (LoS) pada terminal domestik menggunakan pendekatan Space Syntax dan Airport Development Reference Manual (ADRM) 12th Edition. Penelitian menggunakan metode deskriptif kuantitatif melalui Visibility Graph Analysis (VGA) menggunakan DepthmapX untuk menganalisis tingkat integration, connectivity, dan intelligibility pada area utama terminal, meliputi check-in hall, security checkpoint, boarding lounge, baggage claim hall, dan arrival hall. Evaluasi LoS dilakukan berdasarkan beban penumpang jam sibuk, kapasitas antrean, waktu pemrosesan, dan standar kapasitas ruang. Hasil penelitian menunjukkan bahwa terminal memiliki struktur spasial linear yang kuat dengan tingkat integrasi tinggi pada koridor utama sehingga mendukung efisiensi pergerakan dan orientasi penumpang. Namun, beberapa area dengan intensitas pergerakan tinggi, terutama check-in hall dan baggage claim hall, masih menunjukkan performa operasional sub-optimum meskipun secara spasial memiliki kapasitas ruang yang memadai. Penelitian ini menyimpulkan bahwa performa terminal tidak hanya dipengaruhi oleh konfigurasi spasial, tetapi juga oleh kapasitas operasional dan distribusi arus penumpang. Kata Kunci: Konfigurasi Spasial, Tingkat Layanan, Sirkulasi Penumpang, Terminal Bandar udara, Analisis Grafis Visibilitas